Hydromagnetic flow and heat transfer adjacent to an unsteady stretching vertical sheet with prescribed surface heat flux - Aman, Fazlina; Ishak, Anuar; Abdullah Sani, Nur Liyana Aini; Mohd Safuan, Hamizah; Md Shab, Noorzehan Fazahiyah; Jamaian, Siti Suhana; Nor, Maria Elena (2018)
The unsteady hydromagnetic flow adjacent to a stretching vertical sheet is studied. The unsteadiness in the flow and temperature fields is caused by the time dependence of the stretching velocity and the surface heat flux. The governing partial differential equations are reduced to nonlinear ordinary differential equations, before being solved numerically. Comparison with previously published results as well as the exact solution for the steady-state case of the present problem is made, and the results are found to be in good agreement. Effects of the unsteadiness parameter, magnetic parameter, and Prandtl number on the flow and heat transfer are fully examined.